Solid‐State Investigation, Storage, and Separation of Pyrophoric PH3 and P2H4 with α‐Mg Formate. Issue 13 (17th February 2023) - Widera, Anna; Thöny, Debora; Aebli, Marcel; Oppenheim, Julius Jacob; Andrews, Justin L.; Eiler, Frederik; Wörle, Michael; Schönberg, Hartmut; Weferling, Norbert; Dincǎ, Mircea; Grützmacher, Hansjörg
Abstract: Phosphane, PH3 —a highly pyrophoric and toxic gas—is frequently contaminated with H2 and P2 H4, which makes its handling even more dangerous. The inexpensive metal–organic framework (MOF) magnesium formate, α‐[Mg(O2 CH)2 ], can adsorb up to 10 wt % of PH3 . The PH3 ‐loaded MOF, PH3 @α‐[Mg(O2 CH)2 ], is a non‐pyrophoric, recoverable material that even allows brief handling in air, thereby minimizing the hazards associated with the handling and transport of phosphane. α‐[Mg(O2 CH)2 ] further plays a critical role in purifying PH3 from H2 and P2 H4 : at 25 °C, H2 passes through the MOF channels without adsorption, whereas PH3 adsorbs readily and only slowly desorbs under a flow of inert gas (complete desorption time≈6 h). Diphosphane, P2 H4, is strongly adsorbed and trapped within the MOF for at least 4 months. P2 H4 @α‐[Mg(O2 CH)2 ] itself is not pyrophoric and is air‐ and light‐stable at room temperature. Abstract : Phosphane, PH3, is a highly pyrophoric and toxic gas that is often contaminated with H2 and P2 H4 . The inexpensive α‐Mg formate MOF adsorbs up to 10 wt % of PH3 and allows safe handling of phosphane in air. This MOF is moreover a candidate for PH3 purification and longtime P2 H4 storage in air and at room temperature.